Исследование сдвоенных зубчатых планетарных механизмов со степенью подвижности 2 = W, образованных базовыми дифференциалами типа D.AA - Кладова, О. Ю.; Шебанов, И. Г. (НТУ "ХПИ", 2006)
Пропонуються раціональні здвоєнні зубчасті планетарні механізми для приводів співвісних гвинтів.

Research of planetary gears with two degrees of freedom generated by base differentials with two external gearing (D.AA) is presented. For drives of coaxial propellers rational coupled gears are recommended.
Keywords: КПД; сдвоенный механизм; предаточные отношения; масса; скорость; коэффициент полезного действия